PROLAX: PSIKOEDUKASI PERLINDUNGAN LANSIA DARI HOAX PADA ANGGOTA KARANG WERDA “LAROSE” KABUPATEN MALANG - Rakhmaditya Dewi Noorrizki; Nur Rohmah Hidayatul Qoyyimah; Jati Fatmawiyati (LP2M Universitas Hasanuddin, 2024)
When it comes to using technology and the internet, the elderly are a population that is at risk. When it comes to using the internet and communicating in groups, partners' primary issue is that it is simple for the elderly to transfer unreliable information from one group to another. This community service is being done to educate senior residents of Karang Werda